Conselho Fiscal na Governança Corporativa: O caso de uma cooperativa de trabalho médico no Estado de São Paulo - Brasil - Peleias, Ivam Ricardo; dos Santos, Maria Cristina Lourenço; Tinoco, João Eduardo Prudêncio (Revista da FAE, 2017)
O Brasil possui especificidades em suas práticas de gestão e de governança corporativa, dentre elas a implantação e o funcionamento de Conselhos Fiscais, previstos na legislação nacional desde o Século XIX. A existência e o funcionamento de Conselhos Fiscais na fiscalização dos atos de gestão é uma oportunidade de investigar a atuação e contribuições desses órgãos. Este trabalho buscou estudar a atuação do Conselho Fiscal de uma cooperativa de trabalho médico no Estado de São Paulo, comparando a atuação do órgão entre dois períodos de tempo ao longo dos anos 2000: de 2003 a 2004 e de 2005 a 2006. Foram analisados documentos da entidade e do Conselho Fiscal, entrevistou-se o assessor contratado para apoiar o órgão e aplicados questionários aos grupos de conselheiros desses períodos. É um estudo de caso incorporado, com a triangulação das informações obtidas em quatro fontes de dados. Foram usadas as técnicas de análise documental (estatutos da operadora e atas de reunião do Conselho Fiscal), análise de conteúdo (entrevista) e análise de clusters (agrupamento e análise das opiniões dos conselheiros). Os resultados obtidos indicam que a atuação do Conselho Fiscal foi além dos relatórios financeiros, alcançando a gestão. Os conselheiros passaram a conhecer outras questões e a fornecer informações relevantes aos cooperados. Foram constatadas melhorias ao longo do tempo, permitindo que os conselheiros exerçam melhor seu papel, propiciando boas práticas de governança corporativa. Palavras-chave: Conselho Fiscal. Governança Corporativa. Brasil. Contabilidade. Cooperativas de Trabalho Médico. Abstract Brazil has specific characteristics in its business practices and corporate governance, among which the establishment and operation of Fiscal Councils, provided by national law since the nineteenth century. The existence and functioning of Fiscal Councils in the oversight of business actions is an opportunity to investigate the role and contributions of these bodies. This study aimed to study the performance of the Fiscal Council of a medical cooperative in Sao Paulo State - Brazil, comparing the performance of the body between two time periods throughout the 2000s: 2003 to 2004 and from 2005 to 2006. The researchers analyzed documents of the entity and the Fiscal Council, interviewed the advisor hired to support the Fiscal Council and applied questionnaires to groups of fiscal counselors during these two periods. It is an incorporated case study with the triangulation of information obtained from four data sources. The researchers used the techniques of documentary analysis (operator´s by-laws and minutes of Fiscal Council meetings), Content Analysis (interview) and cluster analysis (grouping and analysis of Fiscal Counselor´s opinions). The results indicate that the performance of the Fiscal Council evolved during the study period, going beyond financial reports and reaching management. The Fiscal Counselors got acquainted with other issues and provide relevant information to the Cooperative members. Improvements were verified over time, allowing Counselors to play their role better, providing good corporate governance practices. Key words: Fiscal Council. Corporate Governance. Brazil. Accounting. Medical Work Cooperatives.